FAKTOR-FAKTOR PENYEBAB KETERLAMBATAN PENYELESAIAN STUDI MAHASISWA PROGRAM STUDI JINAYAH SIYASAH UNIVERSITAS ISLAM NEGERI IMAM BONJOL PADANG - Masna Yunita (Turast: Jurnal Penelitian dan Pengabdian, 2022)
Ideally, with the SKS system, students will be able to complete their studies at the earliest within 7 (seven) semesters or 8 (eight) semesters. This is different from the case with Jinayah Siayah Study Program students who mostly complete their studies for more than 8 (eight) semesters and even up to 14 semesters. What is the real cause of the student being late in completing his studies? To get these answers, interviews were conducted with students from the class of 2012, 2013 and 2014 who were late in completing their studies. From the results of these interviews, it can be seen that the cause of the students themselves is that they still do not understand how to make research proposals and do not have research ideas. While the other cause is the length of the thesis guidance process, some even up to 2 years, the thesis guidance process is rarely under 9 (nine) months.